The Effectiveness of Skills Development and Work Motivation on Employee Engagement through Managerial Competencies - Aqila Zayyan; Faizal Mulia Z; Sopyan Saori (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Employee engagement represents a crucial element in enhancing organizational performance and is shaped by multiple organizational and individual factors, including skills development, work motivation, and managerial competencies. This study investigates the influence of skills development and work motivation on employee engagement by considering the mediating role of manager competencies. This study applied a quantitative approach with an explanatory research design. Data were obtained from 51 permanent employees selected through purposive sampling and analyzed using multiple linear regression and the Sobel mediation test in SPSS 27. The findings reveal that skills development and work motivation have positive and significant effects on both employee engagement and manager competencies. In addition, manager competencies positively and significantly influence employee engagement and effectively mediate the relationship between skills development, work motivation, and employee engagement. These results highlight that enhancing employee engagement requires not only continuous efforts to develop employee skills and maintain work motivation but also improving managerial competencies to optimize the impact of these organizational practices. This study enriches the human resource management literature by emphasizing the mediating role of managerial competencies in explaining how skills development and work motivation contribute to employee engagement.